MODULATORY EFFECTS OF PORCINE CARDIAC CRYOEXTRACT ON GLYCOGENOLYSIS IN EXPERIMENTAL MODELS OF MYOCARDIAL DYSTROPHY - ChyzhМ. О.; Hladkykh, F. V.; LiadovaТ. І.; Matvieienko, M. S.; Komorovsky, R. R. (Eastern Ukrainian Medical Journal, 2025)
Background. Myocardiodystrophy represents a severe metabolic disturbance in the cardiac muscle, leading to structural and functional alterations in cardiomyocytes and impaired cardiac performance. One of the key pathological mechanisms is the disruption of glycogenolysis, which negatively impacts myocardial energy metabolism. Considering the critical importance of maintaining energy homeostasis in the heart, biologically active substances derived from cryopreserved xenogeneic heart fragments emerge as a promising therapeutic avenue. Objective. To investigate the effects of an extract from cryopreserved piglet heart fragments on glycogenolysis activity in cardiomyocytes and its potential therapeutic impact in a model of adrenaline-induced myocardiodystrophy (AMD). Methods. The study involved 84 outbred male rats (250–300 g) maintained under standard vivarium conditions. AMD was induced using a single subcutaneous injection of 0.18% adrenaline tartrate solution at a dose of 5 mg/kg. The experimental group received daily intraperitoneal injections of the extract at 50 µg of peptides per 100 g of body weight for 14 days. The control group was administered an equivalent volume of 0.9% sodium chloride solution. Amiodarone (10 mg/kg, intramuscularly) served as a reference drug. Heart tissue homogenates were analyzed post-decapitation. Glycogen content was measured using the glucose oxidase method, and glucose-6-phosphate (G-6-P) levels were determined spectrophotometrically using the hexokinase method. Results. On day 2, rats treated with the extract showed a glycogen level of 3.1±0.14 mg/g (95% CI: 2.8–3.4), a 48.3% increase compared to controls (p=0.007). In the amiodarone group, glycogen reached 4.2±0.06 mg/g (95% CI: 4.1–4.3), a 99.3% increase over controls (p<0.001), yet lower than that in the extract group. By day 14, extract-treated rats exhibited a glycogen level of 8.0±0.30 mg/g (95% CI: 7.4–8.6), up 156.4% from day 2 (p=0.01) and 61.1% from day 7 (p=0.01). On day 14, G-6-P levels in the control group were 0.79 [0.77–0.86] µmol/g, representing a 75.6% increase from day 2 (p=0.01) and 38.6% from day 7 (p=0.05). In the extract group, G-6-P levels reached 0.80 [0.79–0.81] µmol/g, a 56.9% rise from day 2 (p=0.01) and 25.0% from day 7 (p=0.01). The amiodarone group showed G-6-P levels of 0.82 [0.81–0.82] µmol/g, a 57.7% increase from day 2 (p=0.01) and 24.2% from day 7 (p=0.01). Conclusions. The extract from cryopreserved piglet heart fragments demonstrated a significant corrective effect on carbohydrate metabolism disorders in the myocardium of rats with adrenaline-induced myocardiodystrophy. This includes normalization of glycogen and G-6-P levels, highlighting its potential as a therapeutic agent for myocardial ischemic and hypoxic conditions.